The effectiveness of computer-based information systems: definition and measurement - Miller, Jonathan (Department of Information Systems, 2023)
Determining and enhancing the effectiveness of computer-based information systems (1/S) in organisations remains a top priority of managers. This study shows that the essential nature and role of 1/S is changing and that classic views of 1/S effectiveness have become increasingly inappropriate. Drawing on the organisational effectiveness literature, it is argued that user perceptions provide a practical alternative and a conceptually sound basis for defining and measuring 1/S effectiveness. A popular measure - User Information Satisfaction - is examined and empirical studies using this measure are critiqued. This reveal limited theoretical grounding or convergence but a growing emphasis on behavioural theory. Based on prior empirical work by the author and expectancy and motivation theory, a model of 1/S behaviours is offered. The model suggests that fit between the needs of the organisation and the capability of 1/S to satisfy these needs is essential to achieving 1/S effectiveness. Several hypotheses are formulated. The development and validation of a particular measurement instrument is traced. The instrument addresses 37 facets of the overall information systems function and respondents complete perceptual scales tapping the relative importance of these facets and how well each is performed. The instrument is used in a field survey of 1025 managers and 1/S staff in eleven large organisations. Attitudes towards 1/S are found to correlate with perceptions of fit between organisational needs and 1/S capabilities. The survey is complemented by management interviews, document analysis and an assessment of the dynamics of the relevant 1/S groups. Cultural and other features associated with perceived 1/S success are found. It is concluded that perceptions of organisational members are central to the meaning of information systems effectiveness, but that the user information satisfaction construct and purely attitudinal measures are inadequate. Based on the notion of fit, a new definition of 1/S effectiveness is proposed. Guidelines for measurement are presented and it is argued that the instrument used in this study is a satisfactory tool. Specific recommendations for management are made and rich opportunities for future research are identified.